STATISTICAL PROPERTIES OF SINGLE-MODE DISPLACED SQUEEZED VACUUM STATE - Alemayehu Getahun; Ruth Birhanu; Misrak Getahun (International Journal on Orange Technologies, 2020)
In this paper the displaced squeezed vacuum state is produced by application of displaced operator on squeezed vacuum state. With help of density operator we find Q function, with the Q function mean, variance and quadrature variance would be calculated. From this we can determine the system has superpoissonian statics, the squeezed parameter is direct proportion with both mean and variance of photon number, but inversely proportion with quadrature variance. The squeezing occurs in plus quadrature with the maximum squeezing of 99.7% for r=3.